2011
DOI: 10.1186/1743-422x-8-62
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale seroprevalence analysis of human metapneumovirus and human respiratory syncytial virus infections in Beijing, China

Abstract: BackgroundHuman metapneumovirus (hMPV), a recently identified virus, causes acute respiratory tract infections (ARTIs) in infants and children. However, studies on the seroepidemeology of hMPV are very limited in China. To assess the seroprevalence of hMPV infection in China, we tested a total of 1,156 serum specimens for the presence of anti-hMPV IgG antibody in children and adults free of acute respiratory illness in Beijing, China by using hMPV nucleocapsid (N) protein as an antigen. As a control, we used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 33 publications
2
39
1
Order By: Relevance
“…Reports on HMPV infections in otherwise healthy adults are relatively rare. Seroprevalence studies indicated that all adults have been infected with HMPV by the age of 25, with very high seroprevalence rates beginning from 5 years of age (68,147,150,153,255,261,262). The nosocomial impact of HMPV is estimated to be as high as that for RSV.…”
Section: Clinical Epidemiologymentioning
confidence: 99%
“…Reports on HMPV infections in otherwise healthy adults are relatively rare. Seroprevalence studies indicated that all adults have been infected with HMPV by the age of 25, with very high seroprevalence rates beginning from 5 years of age (68,147,150,153,255,261,262). The nosocomial impact of HMPV is estimated to be as high as that for RSV.…”
Section: Clinical Epidemiologymentioning
confidence: 99%
“…These findings suggest that HMPV circulated in the human population long before it was identified as an etiological agent (4,(12)(13)(14). Recent seroprevalence studies have shown that HMPV steadily circulates in the community, as evidenced by the 100% seropositivity in adults aged 20 years and Ͼ65 years, which also suggests a steady reinfection rate that maintains measurable anti-HMPV IgG titers in the population (15)(16)(17). In agreement with this notion, epidemiological studies have concluded that HMPV displays a broad spatiotemporal distribution, affecting industrialized and developing countries equally.…”
Section: Introductionmentioning
confidence: 86%
“…To date, there has been no study demonstrating direct deleterious effects of HMPV on the humoral immune response of humans and model animals. However, independent studies have shown that healthy adults become reinfected, either experimentally (34) or naturally, in the face of 80 to 100% seroprevalence against HMPV (15,216,217), suggesting that HMPV may have evolved mechanisms that interfere with the proper development of antibody-dependent immunity. Along this line, others have proposed that the humoral response plays a minor role in the clearance of HMPV (16) based on the observation that HMPV recirculates in the population despite the fact that humans of all age groups maintain significant titers of neutralizing antibodies.…”
Section: Impairment Of DC Function By Hmpv and Implications For The Gmentioning
confidence: 99%
“…The anti-rDBP IgG antibodies produced in immunized mice were measured by ELISA assay, as described elsewhere [33]. Purified rDBPs were used as coating antigens (0.25 µg/mL) for the ELISA assay.…”
Section: Methodsmentioning
confidence: 99%